Bank Profitability: A View on Macroeconomic and Internal Factors of KBMI 2, 3 and 4 - Putra, Yohan Fernanda; SS, Vietha Devia (Contemporary Studies in Economic, Finance and Banking, 2026)
In carrying out intermediation activities to generate profits, banks face various factors influencing their financial performance, encompassing both macroeconomic and bank-specific factors. This study aims to analyze the impact of macroeconomic and bank-specific factors on profitability, measured by Return on Assets (ROA). The sample in this study includes banks listed on the Indonesia Stock Exchange (IDX) with a minimum core capital of 6 Trillion rupiah during the period Q1 2018 to Q4 2024. This study uses a dynamic panel data regression model with the Generalized Method of Moments - System (GMM) approach to address endogeneity problems and provide more accurate estimations. The research findings indicate that Inflation, BI Rate, and Net Interest Margin (NIM) have a significant positive effect on ROA. Conversely, Credit Growth (CG) and Operating Expenses to Operating Income (BOPO) have a significant negative effect on ROA. Meanwhile, Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) do not have a significant effect on ROA. The results of this study can be utilized by regulators and stakeholders to optimize banking performance and health amidst fluctuating macroeconomic conditions.